The bubble size distribution and its evolution in non-yeasted wheat flour doughs investigated by synchrotron X-ray microtomography. (February 2016) - Koksel, Filiz; Aritan, Serdar; Strybulevych, Anatoliy; Page, John H.; Scanlon, Martin G.
Abstract: Determination of the bubble size distribution at the end of mixing and controlling its changes are the basis for improving bread quality before it is fully manufactured. X-rays from a synchrotron source (Biomedical Imaging and Therapy beamline, Canadian Light Source) were used to rapidly characterize the bubble size distribution and its evolution in non-yeasted dough subsamples as a function of time for 3 h following mixing. A complete X-ray microtomography scan was completed within 120 s. The higher number density of bubbles in dough compared to results previously reported in the literature was attributed to the better contrast and higher resolution (smaller pixel size, 8.75 μm) of the reconstructed X-ray images generated from synchrotron X-rays. The bubble size distribution was very well characterized with a lognormal distribution function. This distribution had a median bubble radius of 22.1 ± 0.7 μm at 36 min after the end of mixing which increased to 27.3 ± 0.7 μm over 162 min, a trend indicative of transport of gas in the dough due to disproportionation. This is the first time disproportionation in non-yeasted wheat flour doughs has been monitored directly under bulk conditions relevant to dough in bakery conditions. These results show that the diffusion-driven dynamics of bubbles in non-yeasted bread doughs can be followed by X-rays from a synchrotron source via feature extraction using image analysis software. Highlights: We use synchrotron X-rays to characterize the bubbly structure of nonyeasted doughs. The bubble size distribution is very well characterized lognormally. Median of lognormal bubble size distributions grows with time due to gas transport. Disproportionation is monitored using a synchrotron source for the first time New insights on bubble dynamics in dough made without yeast obtained.